Varying Teaching Styles for Learning Styles Differences - Shokira Linda Vinde (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The aim of this research was to investigate teachers’ teaching styles variation as a way to solve problems related to students’ learning styles differences during teaching and learning process. The research was a type of qualitative research describing the phenomenon of teachers’ ways to vary their teaching styles. This study was conducted in IAIN Padangsidimpuan toward a teacher teaching in a classroom consisting of 26 students. To collect the data, questioners were given to students; interview and observation were given to teacher. Then, descriptive data analysis was implemented in analyzing the data that were collected. The research found that from the 26 students, 6 students are visual learners, 8 students are audio learners, 2 students are verbal learners and 10 students are kinesthetic learners. In relation to teachers’ teaching styles variation, it was seen that almost all of the teachers’ teaching styles were directed to fulfill all the needs of students’ styles differences. Particularly, the dominant teaching styles were suitable for kinesthetic learners and this is good because most of the students are regarded as kinesthetic. However, the teacher also could vary her teaching to meet all learning styles